Treatment algorithm for Hirschsprung disease at children - N. M. Leonevskaya; S. I. Erdes; M. A. Ratnikova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
Issues of diagnostics, classification, variants of clinical manifestations of Hirschsprung disease (HD) at children of various age are presented. Treatment approaches, variants of surgical intervention (advantages, disadvantages, complications), prognosis at this disease areconsidered. Clinical demonstration of 10 years old childwith HD is presented.